(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Technology has played a vital role in the evolution of Indian banking sector through speed, accuracy, efficiency, promptness and reduction in cost. Banking services are now tilting to “Anywhere Anytime banking” aspect. Today banks are providing services through different automated channels like ATM, Debit Card, Credit Cards, Internet Banking, Mobile Banking, Phone Banking, RTGS, NEFT and ECS etc. Mobile banking is a system of providing services to the customers to carry out banking transactions on the ’Mobile Phone’ through a cellular service provider. Mobile Banking is gaining increasing acceptance amongst various sections of the society. The objective of the proposed paper is to study the customer satisfaction towards mobile banking services provided by various banks operating in Delhi and NCR. To achieve the objective of the study, primary data was collected through a structured questionnaire from the respondents using mobile banking services (public, private and foreign banks). In total, 187 respondents were studied with the help of a convenience sampling method. To analyze the collected data, SPSS version 19 was used. The various statistical techniques used for analysis and achieve the objectives of the study are frequency distribution along with percentages, mean, standard deviation. To test the null hypothesis, parametric tests such as t test and ANOVA was used. The major findings of the study reflected that ’sector of the banks’, ’occupation of respondents’ and ’age of the respondents’ has significant impact on customer satisfaction. The study provides meaningful direction to bank managers and decision makers to improve their service quality for higher customer satisfaction.